Zom-B underground - Shan, Darren (Shan, Darren. Zom-B (Series), 2013)
"Waking up in a military complex, months after zombies attacked school, B has no memory of the last few months. Life in the UK has turned tough since the outbreak, and B is woven into life -- and battle -- in the new military regime quickly. But as B learns more about the zombies held in the complex and the scientists keeping them captive, unease settles in. Why exactly was B saved? And is there anyone left in the world to trust?" --